KEANEKARAGAMAN JENIS VEGETASI PENYUSUN HUTAN MANGROVE DI DESA MEDAN MAS KABUPATEN KUBU RAYA - Nasir, Muhammad; Burhanuddin, .; Dewantara, Iswan (JURNAL HUTAN LESTARI, 2019)
This study was conducted to determine the diversity of vegetation species that compose mangrove forests in the village of Medan Mas, Kubu Raya Regency. Measured parameters of important value index , dominance index (C), species richness index (RI), species evenness index (e) was carried out using the survey method by means of a plot. The placement of the research path was done (purposive ). The path made in this study is 10 meters wide (5 m to the left 5 m to the right) and the path length is adjusted to the conditions in the field to the river boundary. From the pathway, a sub-plot is made with a size of 10 m x 10 m for the tree level, and 5 m x 5 m for the sapling level and 2 x 2 for the seedling level. The results of this study indicate that the types found in the field amounted to 12 species for seedlings, 10 species for saplings and 9 species for trees. . Based on the results of the data obtained, it is known that the index value of species diversity (H) at seedling, sapling and tree levels shows a number <1. This means that the value of species diversity found in mangrove forests in Medan Mas Village is relatively low. Forests with low species diversity values indicate that the forest area has experienced forest disturbance or damage. When data collection is carried out in the field, there are several locations that experience disruption or damage in the form of logged-over or transfer functions as shrimp ponds.Keywords: Mangrove Forest, Vegetation Diversity